5-(Furan-2-yl)-4-(p-tolyl)-2,4-dihydro-1,2,4-triazole-3-thione - Dege, N; Andac, O; Cansiz, A; Çetin, A; Sekerci, M; Dinçer, M (Int Union Crystallography, 2004)
In the title Molecule, C13H11N3OS, the triazole plane forms dihedral angles of 3.8 (2) and 81.3 (2)degrees with the furan and p-tolyl ring planes, respectively. In the crystal structure, the molecules exist as centrosymmetric N-H...S hydrogen-bonded dimers, with an N...S distance of 3.312 (2) Angstrom. The packing is further stabilized by C-H...O, C-H...N, C-H...pi and pi-pi interactions.